Eosinophil cationic protein and histamine production by neutrophils from patients with periodontitis. Issue 2 (20th February 2018) - Ribas, David; Fernández‐Carranco, M. Carmen; Hajji, Nabil; Bobadilla, Pedro; Monteseirín, Javier
Abstract: Background: Periodontitis develops through an inflammatory process caused by an infection at the microbial biofilm, followed by tissue destruction mediated by leukocytes, which cause clinically significant destruction of connective tissue and bone. Several elements derived from the bacteria cause the inflammatory response and the release of mediators involved in destruction of the periodontium. There are number of inflammatory mediators released by leukocytes, mainly neutrophils, upon bacterial challenge. Neutrophils produce and release eosinophil cationic protein (ECP) and histamine, two important inflammatory mediators; however, their role has not been characterized in periodontal inflammation. Thus, the purpose of this study is to investigate whether neutrophils from patients with periodontitis can produce ECP and histamine in response to lipopolysaccharides (LPSs). Methods: ECP and histamine production in response to LPSs was analyzed by enzyme‐linked immunosorbent assay. Expression of the histidine decarboxylase and ECP was also analyzed by flow cytometry and fluorescence microscopy in neutrophils from patients with periodontitis in response to LPS. Results: It was found that neutrophils from patients with periodontitis express higher levels of histidine decarboxylase and ECP than those from healthy volunteers, and they also release higher levels of histamine. Conclusion: Findings described could represent new knowledge indicating neutrophils as a source of histamine and ECP in the progression of periodontitis.